Implementation of Security Standards for Facilities and Infrastructure at Integrated Islamic Junior High School LHI Yogyakarta - Laksana, Inggil; Junaedi, Erik (Proceeding International Conference on Religion, Science and Education, 2025)
This research aims to examine the implementation of safety standards for facilities and infrastructure at Integrated Islamic Junior High School LHI Yogyakarta. A descriptive qualitative approach was used to explore in-depth information regarding practices and perceptions related to security in the school environment through observation, interviews and documentation. The research results show that Integrated Islamic Junior High School LHI Yogyakarta has implemented comprehensive physical security standards, including strong building construction, CCTV surveillance systems, fire protection, and clear evacuation routes. Safety management is also implemented through standard operational guidelines (SOP) which include emergency procedures for all school residents. Regular safety training programs, such as evacuation simulations and the use of fire extinguishers, are also implemented to increase preparedness. Even though there are several technical obstacles such as CCTV blind spots and limited backup power, the school is committed to continuing to improve security standards gradually in accordance with budget allocations. Development plans include the addition of CCTV, improvements to stair access and the installation of an automatic alarm system. A holistic approach involving coordination of all school elements is recommended to ensure more effective and sustainable implementation of security standards, creating an increasingly safe and conducive learning environment for all school members.